Ebola virus disease nosocomial infections in the Democratic Republic of the Congo: a descriptive study of cases during the 2018–2020 outbreak. (February 2022) - Baller, April; Padoveze, Maria Clara; Mirindi, Patrick; Hazim, Carmen Emily; Lotemo, Jonathan; Pfaffmann, Jerome; Ndiaye, Aminata; Carter, Simone; Chabrat, Marie-Amelie Degail; Mangala, Samuel; Banzua, Berthe; Umutoni, Chantal; et al.
Highlights: Health workers were among those most affected by nosocomial Ebola virus disease (EVD) in this outbreak. Children had a higher case fatality rate compared with other patients with nosocomial EVD. Referral health facilities and privately owned health facilities had the highest number of nosocomial infections (NI). Clear case definition of NI is required to prompt transmission chain interruption. ABSTRACT: Objectives: To describe the characteristics of nosocomial cases of Ebola virus disease (EVD) in the Democratic Republic of the Congo between July 2018 and May 2020 in order to inform future interventions. Methods: Nosocomial cases of EVD were identified during outbreak response surveillance, and a retrospective analysis of cases was conducted according to demographic characteristics and type of health facility (HF). Results: Of 3481 cases of EVD, 579 (16.6%) were nosocomial. Of these, 332 cases occurred in women (57.3%). Patients and visitors accounted for 419 cases (72.4%), of which 79 (18.9%) were aged 6–≤18 years and 108 (25.8%) were aged ≤5 years. Health workers (HWs) accounted for the remaining 160 (27.6%) nosocomial cases. The case fatality rate (CFR) for HWs (66/160, 41.3%) was significantly lower than the CFR for patients and visitors (292/419, 69.7%) ( P <0.001). The CFR was higher among cases aged 6–≤18 years (54/79, 68.4%) and ≤5 years (89/108, 82.4%). Referral HFs (>39 beds) had the highest prevalence of nosocomial EVD (148/579, 25.6%). Among HFs with at least one case of nosocomial infection, 50.0% (98/196) were privately owned. Conclusions: Nurses and traditional healers should be targeted for infection prevention and control training, and supportive supervision should be provided to HFs to mitigate EVD transmission.